2014
DOI: 10.1155/2014/562804
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic Antimicrobial Effects of Mixtures of Ethiopian Honeys and Ginger Powder Extracts on Standard and Resistant Clinical Bacteria Isolates

Abstract: Purpose. To evaluate antimicrobial effects of mixtures of Ethiopian honeys and ginger rhizome powder extracts on Staphylococcus aureus (ATCC 25923), Escherichia coli (ATCC 25922), Staphylococcus aureus (MRSA), Escherichia coli (R), and Klebsiella pneumoniae (R). Methods. Agar diffusion and broth assays were performed to determine susceptibility of these standard and resistant clinical bacteria isolates using honey-ginger powder extract mixtures. Results. Honey-ginger powder extract mixtures produced the highes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 32 publications
1
26
3
1
Order By: Relevance
“…72 Honey also has synergistic antimicrobial action with natural materials as chitosan 73 and ginger powder extract. 74 Otherwise, EEP showed synergistic antimicrobial effect with antibiotics {oxacillin, 27 clarithromycin, 75 cefazolin, 76 ciprofloxacin 50 cefixime 77 and many different antibiotics 27,53,66,69 } or essential oils of ginger, 78 garlic, 79 cinnamon, 80 clove, 78 or chitosan. 81 The study concluded that Egyptian fennel honey and EEP have potent antimicrobial activity against biofilm producing MRSA, while both apiproducts revealed more potency and synergy will be achieved against these foodborne pathogens.…”
Section: Resultsmentioning
confidence: 99%
“…72 Honey also has synergistic antimicrobial action with natural materials as chitosan 73 and ginger powder extract. 74 Otherwise, EEP showed synergistic antimicrobial effect with antibiotics {oxacillin, 27 clarithromycin, 75 cefazolin, 76 ciprofloxacin 50 cefixime 77 and many different antibiotics 27,53,66,69 } or essential oils of ginger, 78 garlic, 79 cinnamon, 80 clove, 78 or chitosan. 81 The study concluded that Egyptian fennel honey and EEP have potent antimicrobial activity against biofilm producing MRSA, while both apiproducts revealed more potency and synergy will be achieved against these foodborne pathogens.…”
Section: Resultsmentioning
confidence: 99%
“…Ewnetu et al, in 2014 [ 18 ], assessed the antimicrobial effects of mixtures of Ethiopian honeys and ginger rhizome powder extracts separately and in combination on several pathogenic bacteria. Their results confirmed our findings regarding the favorable antibacterial activity of ginger.…”
Section: Discussionmentioning
confidence: 99%
“…The usage of honey in combination with other antimicrobial agents has been the subject of some investigations. [183][184][185] Combining honey with other antimicrobial agents diminishes the chances of pathogen survival after exposure, consequently reducing the likelihood of emergence of resistant bacteria. The usage of manuka honey, in combination with the antibiotics tobramycin and colistin, to combat P aeruginosa and Burkholderia cepacia infections resulted in synergistic or additive effects against the 2 strains of each bacterial species.…”
Section: The Usage Of Honey In Combination With Other Antimicrobial Amentioning
confidence: 99%